45.0k views
2 votes
What is the solution to the equation 5x + 2(x − 4) = 5x + x − 10? (1 point)

User TrOnNe
by
4.7k points

2 Answers

4 votes

Answer:

x= -2

Explanation:

IM TO COOOL FOR EXPLAINING

User Kaliatech
by
4.4k points
7 votes

Answer:

-2 = x

Explanation:

Using the Distributive Property of Multiplication and combining like-terms will give you this:

7x - 8 = 6x - 10

-7x -7x

-----------------

-8 = -x - 10

10 +10

------------

2 = -x [Divide by -1]

-2 = x

I am joyous to assist you anytime.

User Suvonkar
by
5.2k points